(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article presents an analysis of the verbal-semantic level of the linguistic personality of Grigory Pechorin based on the material of the film adaptation of M. Lermontov’s novel “A Hero of Our Time”. The lexical analysis of the main character of the film adaptation was carried out according to the three-levelled system proposed by Yu. Karaulov. At the first stage of the study, all the hero’s replicas were selected by the method of continuous sampling. Further, all the selected words were distributed by macroclasses (parts of speech), and within macroclasses – by semantic fields and concretizing subgroups. A quantitative analysis of the selected unique words and their word usage in the hero’s speech made it possible to establish that pronouns prevail over all parts of speech in terms of the number of word usage. It can be explained by the fact that the object of research is one of the varieties of discourse – hero’s speech which is surrounded by real life, and, as you know, even depicted colloquial speech usually tends to a certain degree of similarity to real colloquial speech, which determines the role of the environment within the text fragments with direct speech. Indicating words (pronouns) can be considered as such an environment since they are verbal means of explicating the elements of a modelled communicative situation. While in terms of the number of positions, verbs prevail over all parts of speech. The numerical superiority of adjectives over adverbs in terms of the number of positions and the priority of adverbs over adjectives in terms of word usage was also noted.